Pollination-system diversity in Epipactis (Orchidaceae): new insights from studies of E. flava in Thailand - Henrik Pedersen (2018)
© 2018 Springer-Verlag GmbH Austria, part of Springer Nature The rewarding orchid Epipactis flava was studied in NW Thailand. Its flowers were visited by a wide range of insects, most of which served as pollinators. The most frequent pollen bearers were (in decreasing order): the cricket Homoeoxipha lycoides, stingless bees of the Tetragonula testaceitarsis/hirashimai complex, hoverflies of subfam. Syrphinae, the wasp Polybioides gracilis and sweat bees of subfam. Halictinae. We found no evidence of a link between the rheophytic habit of E. flava and its pollinator fauna. Whereas most pollinators visited the flowers to feed on nectar, females of Episyrphus alternans (Syrphidae: Syrphinae) were observed to oviposit despite the absence of prey for their young. Hence, we suggest that dual pollination systems contribute to the opportunist strategy of E. flava, and we discuss, in a phylogenetic framework, how the strategy fits in with those previously reported for Epipactis sect. Arthrochilium. The elastic attachment of the epichile (a universal trait in sect. Arthrochilium) was found to promote outcrossing, and we hypothesize that loss of the elastic hinge has provided a key innovation facilitating recurrent evolution of obligate autogamy in sect. Epipactis (which is nested in sect. Arthrochilium).